Mendelian and non-mendelian mutations affecting surface antigen expression in Paramecium tetraurelia. - Epstein, L M (1984)
A screening procedure was devised for the isolation of X-ray-induced mutations affecting the expression of the A immobilization antigen (i-antigen) in Paramecium tetraurelia. Two of the mutations isolated by this procedure proved to be in modifier genes. The two genes are unlinked to each other and unlinked to the structural A i-antigen gene. These are the first modifier genes identified in a Paramecium sp. that affect surface antigen expression. Another mutation was found to be a deletion of sequences just downstream from the A i-antigen gene. In cells carrying this mutation, the A i-antigen gene lies in close proximity to the end of a macronuclear chromosome. The expression of the A i-antigen is not affected in these cells, demonstrating that downstream sequences are not important for the regulation and expression of the A i-antigen gene. A stable cell line was also recovered which shows non-Mendelian inheritance of a macronuclear deletion of the A i-antigen gene. This mutant does not contain the gene in its macronucleus, but contains a complete copy of the gene in its micronucleus. In the cytoplasm of wild-type animals, the micronuclear gene is included in the developing macronucleus; in the cytoplasm of the mutant, the incorporation of the A i-antigen gene into the macronucleus is inhibited. This is the first evidence that a mechanism is available in ciliates to control the expression of a gene by regulating its incorporation into developing macronuclei.